The Foreigner (Columbia TriStar Home Entertainment, 2002)
Steven Segal is John Cold, a professional secret agent for hire who's as cunning as he is deadly. Enter his treacherous world and you might not come out alive. Political corruption, murder and a bounty of backstabbing bad guys swarm around a mysterious package that Cold is hired to deliver from France to Germany. Some very dangerous people will stop at nothing to make sure that Cold doesn't get the package to its rightful recipient, but they'll soon find out that getting his way is a hazardous decision.